Fatigue life behaviour of glass/kenaf woven-ply polymer hybrid biocomposites - Dhar Malingam, Sivakumar; Ng, Lin Feng; Lau, S. M.; Lim, K. T. (Springer New York LLC, 2017)
Investigation on the fatigue life of hybrid composites is critical to extend their applications and acceptance among industries; however, there is a lack of research focus on fatigue performance of the hybrid composite. In this study, the fatigue life of glass/kenaf woven-ply hybrid composite with thermoplastic and thermoset polymer matrix was investigated. Hybrid composites consist of two different fibre configurations: kenaf/glass/kenaf and glass/kenaf/glass. Thermoplastic hybrid composites were manufactured through the hot press moulding compression method, while thermoset hybrid composites were fabricated through the vacuum-assisted resin infusion method. The tensile strength and fatigue strengths of the kenaf/glass/kenaf composite have been identified to be significantly lower than those of the glass/kenaf/glass composite regardless of the types of matrix used. However, thermoplastic-based kenaf/glass/kenaf composites are less fatigue sensitive compared to glass/kenaf/glass composites; however, this phenomenon is vice versa for thermoset composites due to the epoxy matrix, which limits the stiffening effect in natural fibres.